Peran Pemerintah Dalam Ekonomi Islam - Abdul Ghafur; Nurul Fadila (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2020)
It is acceptable for the government play an important role in the economy. Development. For example, through public sector policy, the government plays an important role in driving economic growth. However, there seems to be debate in the business literature about whether government should play a role in de-economic development. This article expands the role of government in economic development, which is prevalent in the economic literature. If it seems that there are two opposing poles discussing whether governments should play a role in economic development, this article shows that thematic differences only talk about how many governments play a role. must play in economic development. This article explains the role of government in economic development.